A report of the species of the genus Phyllobothrium radioductum (Eucestoda: Phyllobothridae) from Trygon sephen at Ratnagiri (MS), India - Khamkar, D D (Journal of Experimental Sciences, 2012)
The present form deals with redescription of species of the genus Phyllobothrium radioductum (Beneden, 1849), Maire weir kay, 1942 which is having some additional characters, such as Testes 90-95 (92), ovary indistinctly bilobed, large, transversely placed near the posterior margin of the segment, shape and structure of vitellaria (granular, thin strips).